Water Resource Conservation: Need for sustainable food crop production - Palanichamy, A.P. (Food Biology, 2011)
India is extremely rich in water resources. The country is endowed with large network of great rivers and vast alluvial basins to hold ground water. By virtue of its peculiar placement in the foothills of the magnify Himalayas and having the ranges of Sathpoora, Aravali and the decade plateau running through it the country has huge water resources which have been meagerly tapped. Over water resources can be divided into two broad categories viz., the surface water resources and the ground water resources. Each of these is a part of the earthÃ¢â‚¬â„¢s water circulatory; system called the hydrologic scale and each is ultimately derived from precipitation i.e., rainfall and snow. A part of the annual rainfall is held up in the undulating land surface and seeps down beneath it to give subsoil water resources.Ã‚Â The amount which thus does not seep down flows in the form of streams and unions, the river system, another part which evaporates, forms moisture in the atmosphere which may another clouds, rain and snow.Ã‚Â Thus all forms of water resources are inter dependent as the loss of one may be the gain of the other.